The influence of discipline and allowances on employee performance through job satisfaction as a mediating variable evidence - Bella Febiola; Muhammad Donal Mon; Agustinus Setyawan (Jurnal Manajemen dan Pemasaran Jasa, 2024)
The objective of this study is to examine the impact of discipline and allowances on employee performance, using job satisfaction acting as a mediator. This study implements quantitative research methodology. The population under study comprises all employees of BP Batam, amounting to a total of 2,287 individuals. The study included a sample size of 340 employees, which were picked using the Simple Random Sampling approach. The data utilized in this investigation consists of primary data, acquired through the dissemination of questionnaires. The Likert scale is employed as the measurement scale. The research utilizes the quantitative data analysis approach known as Partial Least Square (PLS) method. The study findings suggest that both punishment and allowances have a good and considerable influence on employee performance, both directly and indirectly, by means of job satisfaction as a mediator. This implies that effective self-control and sufficient financial provisions might enhance job contentment, resulting in enhanced employee productivity.